Typical application of carbon made of Malaysia oil palm Kernel Shell - 284026 Fadil Othman; Mohd. Razman Salim; Johan Sohaili; World Conference on Environmental Management : Facing Changing Condition ([200-] : Bangi, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
10